A Comparison of Invasive Airway Management and Rates of Pneumonia in Prehospital and Hospital Settings. (2nd October 2015) - Andrusiek, Douglas L.; Szydlo, Danny; May, Susanne; Brasel, Karen J.; Minei, Joseph; van Heest, Rardi; MacDonald, Russell; Schreiber, Martin
Abstract: Introduction. Infection is a major cause of morbidity and mortality in trauma. Infection in trauma is poorly understood. The impact of prehospital invasive airway management (IAM) on the incidence of pneumonia and health services utilization is unknown. We hypothesized that trauma patients exposed to prehospital IAM will suffer higher rates of pneumonia compared to no IAM or exposure to IAM performed in the hospital. We hypothesized that patients who develop pneumonia subsequent to prehospital IAM will have longer intensive care unit (ICU) and hospital length of stay (LOS) compared to patients who acquired pneumonia after IAM performed in the hospital.Methods. This is an observational cohort study of data previously collected for the Resuscitation Outcomes Consortium hypertonic resuscitation randomized trial. Patients were included if traumatic injury resulted in shock, traumatic brain injury, or both. Patients were excluded if they died 24 hours after injury, or pneumonia data were missing. Adjusted and unadjusted logistic regression was used to calculate the odds ratio of pneumonia if exposed in the prehospital setting compared to no exposure or exposure in the hospital.Results. Of 2, 222 patients enrolled in the hypertonic resuscitation trial, 1, 676 patients met enrollment criteria for this study. Four and a half percent of patients suffered pneumonia. IAM in the prehospital setting resulted in 6.8-fold increase (C.I. 2.0, 23.0, p = 0.003) in the adjusted odds of developing pneumonia compared to not being intubated, while in-hospital intubation resulted in 4.8-fold increase (C.I. 1.4, 16.6, p = 0.01), which was not statistically significantly different to the odds ratio of prehospital IAM. There were no statistically significant increases in health services utilization resulting from pneumonia incurred after IAM.Conclusion. Exposure to IAM in prehospital and hospital settings results in an increase in pneumonia, but there does not appear to be a link between the source of pneumonia and an increase in ICU or hospital LOS.Keywords: emergency medical services; endotracheal intubation; pneumonia; infection; health services utilization